The effect of Flipped Digital Classroom and student engagement on English writing skills - Farida Ariani; Martin Kustati; Reflianto Reflianto; Novi Yanti; Joni Indra Wandi (Universitas Syiah Kuala, 2024)
Incorporating digital-based learning is crucial for fostering self-directed learning among students. Various digital media platforms, such as Google Classroom, Zoom Meetings, and social media, motivate students to actively engage in their studies. This study aims to assess the effectiveness of the Flipped Digital Classroom (FDC) method on student engagement and English writing proficiency. It employs a quasi-experimental 2x3 factorial pretest-post-test non-equivalent group design and collected data through the Student Engagement in Schools Questionnaire and an English writing test. The FDC group receives pre-recorded lectures, additional reading materials, and online writing assignments before face-to-face discussions, while the control group follows a lecture-based approach with assignments. The analysis involves 48 FDC students and 51 controls, categorized by engagement levels (high, medium, low). Validity and reliability tests are conducted on the questionnaire data, rated on a 5-point Likert scale, while English proficiency is assessed using an English Writing Test. Hypothesis testing utilizes descriptive and inferential statistics, including Two-Way ANOVA. The results indicate a significant 18-point increase in English writing scores for FDC students compared to controls. Furthermore, an interaction analysis reveals a considerable positive impact of method and engagement level on writing skills (p=0.00). English language instructors are encouraged to adopt the FDC method to enhance student engagement and academic achievement in English writing literacy through technology-based learning.